Liver resection in Cirrhotic liver: Are there any limits?. (October 2020) - Chan, Albert; Kow, Alfred; Hibi, Taizo; Di Benedetto, Fabrizio; Serrablo, Alejandro
Abstract: Liver resection remains one of the most technically challenging surgical procedure in abdominal surgery due to the complex anatomical arrangement in the liver and its rich blood supply that constitutes about 20% of the cardiac output per cycle. The challenge for resection in cirrhotic livers is even higher because of the impact of surgical stress and trauma imposed on borderline liver function and the impaired ability for liver regeneration in cirrhotic livers. Nonetheless, evolution and advancement in surgical techniques as well as knowledge in perioperative management of liver resection has led to a substantial improvement in surgical outcome in recent decade. The objective of this article was to provide updated information on the recent developments in liver surgery, from preoperative evaluation, to technicality of resection, future liver remnant augmentation and finally, postoperative management of complications. Highlights: Indocyanine green clearance test and CT volumetry provide useful and accurate preoperative liver function assessments. Liver scintigraphy may provide an alternative tools for assessment in the future. Knowing the appropriate surgical manoeuvres to minimize blood loss conferred safety and feasibility in hepatectomy for cirrhotic livers. Minimally invasive liver surgery conferred better short-term postoperative outcomes with regard to pain control, blood loss and hospital stay in comparison with open approach. Both PVE and ALPPS provided similar efficacy in future liver remnant augmentation with similar short-term outcomes. Vigilance for subtle clinical signs allowed early detection of post-hepatectomy complications. A timely referral for liver transplantation in post-hepatectomy liver failure would change the course of illness.